2008
DOI: 10.1111/j.1365-2729.2008.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of animations on verbal interaction in computer supported collaborative learning

Abstract: This paper focuses on the interaction patterns of learners studying in pairs who were provided with multimedia learning material. In a previous article, we reported that learning scores were higher for dyads of an 'animations' condition than for dyads of a 'static pictures' condition.Results also showed that offering a persistent display of one snapshot of each animated sequence hindered collaborative learning. In the present paper, further analyses of verbal interactions within learning dyads were performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…Referring to the split-attention effect (Chandler and Sweller 1991), we use the expression split-interaction effect to account for the interfering management of two sources of interaction. This interpretation in terms of interference between the additional processing of information induced by collaboration and the additional management of a supplementary source of information (the snapshots) is congruent with the analysis of verbal productions of the peers (Sangin et al 2008). The main findings of this analysis showed that pairs provided with snapshots produced fewer verbal interactions than pairs without snapshots.…”
Section: Did Snapshots Help Learning From Multimedia Instruction?supporting
confidence: 79%
“…Referring to the split-attention effect (Chandler and Sweller 1991), we use the expression split-interaction effect to account for the interfering management of two sources of interaction. This interpretation in terms of interference between the additional processing of information induced by collaboration and the additional management of a supplementary source of information (the snapshots) is congruent with the analysis of verbal productions of the peers (Sangin et al 2008). The main findings of this analysis showed that pairs provided with snapshots produced fewer verbal interactions than pairs without snapshots.…”
Section: Did Snapshots Help Learning From Multimedia Instruction?supporting
confidence: 79%
“…Baker and Lund () explored methods to promote reflective interaction in the context of computer‐mediated communication for CSCL during a modeling task in physics. Sangin, Dillenbourg Rebetez, Bétrancourt, and Molinari () investigated the effects of animations on verbal interaction in CSCL, and the results showed that a number of verbal categories were positively related to learning performance. Other researchers compared awareness of cognitive and social behaviour in individual and CSCL environment; the results of their studies indicated that promotion of interaction increased group processing in CSCL (Kirschner, Kreijns, Phielix, & Fransen, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Representative examples include computer simulations (Novak, 2013), computer animations (Sangin, Dillenbourg, Rebetez, Bétrancourt, & Molinari, 2008), intelligent tutoring systems (Hooshyar et al, 2016), animated pedagogical agents (Johnson, Ozogul, & Reisslein, 2014), virtual reality (Merchant et al, 2013), augmented reality (Bressler & Bodzin, 2013), and remote virtual laboratories (Potkonjak et al, 2016). Such technologies are particularly attractive to many contemporary tech-savvy students, as they promote active learning and can be easily and widely adopted at both formal and informal education sites with no requirement for expensive physical facilities and instrumentations.…”
Section: Background Introductionmentioning
confidence: 99%